ANALISIS RASIO KEUANGAN UNTUK MENILAI KINERJA KEUANGAN INDUSTRI SEMEN DI BURSA EFEK INDONESIA - Suprihatmi Sri Wardiningsih, Remmy Mayorado, Untung Sriwidodo & (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2017)
The objective of research was to assess the financial performance of cementindustry using financial ratio analysis. This research was conducted in the cementindustries enlisted in Indonesia Stock Exchange with qualitative and quantitative dataas the types of data used. The data source employed was secondary one in the form ofcompanies’ financial statements published. Technique of analyzing data used wasfinancial ratio analysis with liquidity ratio (performance ratio), profitability ratio(return on equity ratio), solvency ratio (debt to equity ratio), and market ratio (priceearning ratio and dividend yield). The result of research showed that the cementindustries enlisted in Indonesia Stock Exchange, viewed from liquidity, profitability, andsolvency ratios compared between one year and another using industrial average ratio,showed the poor performance, while viewed from market ratio, it showed the goodperformance.Keywords: liquidity ratio, profitability ratio, solvency ratio, market ratio